Recruiting Older Youths Insights from a New Survey of Army Recruits - Rostker, Bernard D. (RAND Corporation, 2014)
The group of high school graduates who did not enlist immediately after graduation but later join the Army has made up a significant and increasing portion of total enlistments. This report presents the results of a survey of 5,000 Army recruits designed to answer questions about why they did not immediately enlist and why they later chose to do so.